Bone‐impacted fibular free flap: Long‐term dental implant success and complications compared to traditional fibular free tissue transfer. (17th December 2015) - Barber, Brittany R.; Dziegelewski, Peter T.; Chuka, Richelle; O'Connell, Daniel; Harris, Jeffrey R.; Seikaly, Hadi
Abstract: Background: The purpose of this study was to compare complications and dental implant success between the bone‐impacted fibula free flap (BIFFF) and the traditional fibular free flap used in mandibular and midface reconstruction. Methods: Retrospective review of all patients undergoing BIFFF or traditional fibular free flap reconstruction from 2001 to 2009 was undertaken. Complications related to the BIFFF and traditional fibular free flap site of reconstruction were compared. Dental implant success rates for each type of flap were compared at 1‐year intervals for 5 years. Results: One hundred fourteen patients underwent 81 BIFFFs and 35 traditional fibular free flaps. No significant difference in complications between BIFFF (20.9%) and traditional fibular free flap (25.7%) reconstruction was observed. Logistic regression analysis revealed only the site as a predictor of both single and multiple complications. At 5 years postimplantation, dental implant success rates were 95.5% and 77.1% for BIFFF and traditional fibular free flap, respectively ( p = .006). Conclusion: BIFFF reconstruction is a novel surgical technique that may improve long‐term dental implant success rates with no additional risk of complications. © 2015 Wiley Periodicals, Inc. Head Neck 38: E1783–E1787, 2016